2016
DOI: 10.1177/1475725716681714
|View full text |Cite
|
Sign up to set email alerts
|

Developing Students’ Creative Self-Efficacy Based on Design-Thinking: Evaluation of an Elective University Course

Abstract: The development of novel and useful ideas is a process that can be described in multiple steps, including information gathering, generating ideas and evaluating ideas. We evaluated a university course that was developed based on design thinking principles which employ similar steps. Our results show that the course was not effective in enhancing students' creative self-efficacy, the belief that they are able to generate novel and useful ideas. Comparison to previous training approaches lead to conclusions on h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 15 publications
(21 reference statements)
1
17
1
Order By: Relevance
“…On the other hand, prior research has also shown that DT does not necessarily yield valued outcomes. For example, Ohly et al (2017) reported students enrolled in a Design Methodology course from five different classes over one year did not self-report they were better able to generate novel and useful ideas by the end of the semester.…”
Section: Lessons From Within Higher Educationmentioning
confidence: 99%
“…On the other hand, prior research has also shown that DT does not necessarily yield valued outcomes. For example, Ohly et al (2017) reported students enrolled in a Design Methodology course from five different classes over one year did not self-report they were better able to generate novel and useful ideas by the end of the semester.…”
Section: Lessons From Within Higher Educationmentioning
confidence: 99%
“…In this regard, the results show that students under a DT intervention improved their creativity skills throughout the study. Some studies also found a positive impact on this outcome after a DT intervention (West et al, 2012), (Saggar et al, 2017), (Clemente et al, 2017), (Benson and Dresdow, 2015), and one reported no impact (Ohly et al, 2016). The decline on facilitators mean score from t1 to t2 showed in Figure 2 is not significant; however, it can also be explained by the higher facilitators' expectations by the end of the course.…”
Section: Discussionmentioning
confidence: 91%
“…In the case of students' self-evaluation, hypothesis 1 could not be supported either, students' scores were lower than peers' evaluation and higher than facilitators evaluation. In the literature we found studies that reported no impact on teamwork after a DT intervention using selfevaluation instruments (Ohly et al, 2016), (Suh et al, 2014); and one reported a negative impact after collecting data from a student survey (Gatchell et al, 2014). Second, regarding Hypothesis 2 we accept that students under a DT intervention improved their problem-solving skills throughout the study.…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy beliefs are important because regardless of their accuracy, they become self‐fulfilling prophesies (Ackerman, Chamorro‐Premuzic & Furnham, 2011; Putwain, Kearsley & Symes, 2012). Moreover, they seem to be more malleable than is personality (Ohly, Plückthun, & Kissel, 2017; Tierney, 2010; Tierney & Farmer, 2011). That is, besides being susceptible to the effects of personality traits, they can also be influenced by family and teachers (Wigfield et al, 1997), friends (Karwowski, 2015), learning orientation, job autonomy, leadership, and knowledge (Gist & Mitchell, 1992; Gong et al, 2009; Tierney & Farmer, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although self‐efficacy beliefs have been related to conscientiousness, creativity, and teamwork, evidence regarding the functional relationship between the four constructs is lacking. Self‐efficacy beliefs can be more easily modified (Ohly, Plückthun, & Kissel, 2017; Tierney, 2010; Tierney & Farmer, 2011) than can peoples’ conscientiousness, which has been found to be relatively stable in working age adults (Borghuis, et al, 2017; Costa & McCrae, 1994; Elkins, Kassenboehmer, & Schurer, 2017). Since the expression of conscientiousness may be modified through self‐efficacy, there are compelling practical benefits to studying self‐efficacy beliefs because they are a viable point of intervention for managers.…”
mentioning
confidence: 99%